2022
DOI: 10.1039/d2va00180b
|View full text |Cite
|
Sign up to set email alerts
|

MIL88-A as a mediator for the degradation of sulfamethoxazole in PS systems: implication of solar irradiation for process improvement

Abstract: The aim of this study was to demonstrate a feasible system that utilize solar irradiation for the activation of persulfate PS using a mediator, MIL88-A, an iron-based MOF since PS...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
1
3
0
Order By: Relevance
“…Thus, the UV/[CuFe(BDC-NH 2 ) S or CuFe(BDC-NH 2 ) D ]/PMS systems were evaluated in seven successive cycles. It was determined that only a slight decrease in the removal efficiency was observed after six cycles, similar to other studies using MOFs as activators for sulfate radical generation [55]. Both CuFe-MOFs showed higher catalytic activity after each run, suggesting high stability.…”
Section: Rhodamine B Removal By Photo-assisted Activation Of Pms Over...supporting
confidence: 84%
See 1 more Smart Citation
“…Thus, the UV/[CuFe(BDC-NH 2 ) S or CuFe(BDC-NH 2 ) D ]/PMS systems were evaluated in seven successive cycles. It was determined that only a slight decrease in the removal efficiency was observed after six cycles, similar to other studies using MOFs as activators for sulfate radical generation [55]. Both CuFe-MOFs showed higher catalytic activity after each run, suggesting high stability.…”
Section: Rhodamine B Removal By Photo-assisted Activation Of Pms Over...supporting
confidence: 84%
“…According to previous studies, the enhancement in catalytic activity of both CuFe-MOFs across successive runs could be explained by the action of the oxidant on the heterogeneous catalyst, generating more defects that increase the contact surface [55]. In addition, the literature reported that bi-metallic, and multi-metallic catalysts have higher stability in comparison with mono-metallic catalysts due to the strong interactions between the metallic species [56].…”
Section: Rhodamine B Removal By Photo-assisted Activation Of Pms Over...mentioning
confidence: 92%
“…Synthesized MIL-88-A characterization methodology was part of a previously conducted research in our laboratory. 33,34…”
Section: Synthesis and Characterization Methodology Of Mil-88-amentioning
confidence: 99%
“…12,13 This technique is environmentally friendly compared to other chemical processes. 16 Radical species, mainly sulfate radicals (SRs), can be formed in homogeneous systems via electron transfer by chemical activation of persulfate (eqn (1)), 24,25 photolysis (UV 254 nm ) (eqn (2)), [26][27][28] thermolysis (eqn (3)), [29][30][31] or in heterogeneous systems where chemical activation can be accomplished using zero-valent iron particles, bi-metallics and tri-metallics iron-based systems, 32 MOFs, 33,34 or magnetite. Metal-organic frameworks (MOFs) [37][38][39] are a novel class of porous materials composed of a metal ion or a cluster of metal ions connected to an organic molecule termed the linker.…”
Section: Introductionmentioning
confidence: 99%